A Paradigm to Discover Biomarkers Associated With Chronic Kidney Disease Progression. Issue 15 (November 2020) - Ali, Ibrahim; Ibrahim, Sara T; Chinnadurai, Rajkumar; Green, Darren; Taal, Maarten; Whetton, Tony D; Kalra, Philip A
Biomarker discovery in the field of risk prediction in chronic kidney disease (CKD) embraces the prospect of improving our ability to risk stratify future adverse outcomes and thereby guide patient care in a new era of personalised medicine. However, many studies that report biomarkers predictive of CKD progression share a key methodological limitation: failure to characterise patients' renal progression precisely. This weakens any observable association between a biomarker and an outcome poorly defined by a patient's change in renal function over time. In this commentary, we discuss the need for a better approach in this research arena and describe a compelling strategy that has the advantage of offering robust and meaningful biomarker exploration relevant to CKD progression.